THE CRIMINAL ACT OF IMPORTING GOODS IN A NOT NEW CONDITION IS LINKED TO THE THE CRIMINAL ACT OF IMPORTING GOODS IN A NOT NEW CONDITION IS LINKED TO THE DECISION OF THE NUNUKAN DISTRICT COURT NUMBER 332/PID.SUS/2022/PN.NNK - Nazhara, Shafira Nazhara Saefuloh; Kholim, Nur (DE'RECHTSSTAAT, 2024)
This research was grounded by the discovery that the crime of importing goods that were not new was connected to the decision of the Nunukan District Court Number 332/PID.SUS/2022/PN NNK in Nunukan. Trade in imported second-hand goods where import and trade activities are prohibited by statutory regulations. Aim of this research is to answer how does the law enforcement conducted by the trade and industry agency District of Nunukan to the existence of import used secondhanding trade and problems in overcoming them. The approach method used in this research is juridical sociology and data analysis technique is descriptive qualitative. Results of the research indicate that the law enforcement conducted District of Nunukan doesn’t go optimally. This is because District of Nunukan haven’t supervised the trade of import used secondhanding so that there are many merchants who sell the import used secondhanding. Beside the agency haven’t socialized the danger of the import used secondhanding to the healt of human. Problem faced by the agency consist of internal and external problems. The internal problems of the limited human resources and infrastructure, the external problems of the less of awareness of merchants and consumer to obey a rule or legislation.